The Use of Forest Refugia by Ungulate After the 2015'Fire in Tesso Nilo National Park, Riau-Indonesia - Wiwid Prayoga; Muhammad Ali Imron (Jurnal Manajemen Hutan Tropika, 2022)
Wildfires in Indonesia 2015 burnt forests in many protected areas, including remaining forests in Tesso Nilo National Park. We investigated the extent to which 2015's wildfires affect the remaining habitat and the spatial distribution of ungulates in the park by using satellite images to identify burnt and unburnt forest patches. Habitat conditions and the presence of ungulates indicated by the number of ungulate signs were compared between burnt and unburnt areas. The fire devastated trees at different rates depending on tree life form stages. We found that younger trees were more vulnerable to fire. The abundance of ungulates did not differ significantly between burnt and unburnt areas, but all vegetation characteristics were significantly different (Mann-Whitney U-test p-value < 0.05). We surmise that food such as new shoots or leaves, particularly at the edge of burnt areas, attracted ungulates out of unburnt areas. The remaining forest is relatively small, and the park is under continued pressure from illegal conversion, so any further loss of remaining forest as refugia will likely harm the ungulate population. We recommend that management should prioritize the preservation of remaining pristine habitat and the reduction of fire suppression, especially during the dry season.